Motivations for participating in a non-interventional gender-based violence survey in a low-income setting in South Africa - Yandisa Sikweyiya; Mzikazi Nduna; Nwabisa Shai; Rachel Jewkes (BMC, 2017)
Abstract Background Qualitative study of motivations to participate in research into violence and other sensitive issues can help interpretation of findings from community based quantitative surveys. It is equally important to conduct research that may enable a deeper understanding on what motivates people to participate in GBV studies. To date, not much research has been conducted to investigate the factors that influence non-enrolment and enrolment in GBV studies from the viewpoint of the real participants. The present study sought to explore people's reasons for participating in a non-intervention GBV community-based survey in Gauteng province, South Africa. Methods Twenty-two qualitative in-depth interviews were conducted with adult black African men and women who had participated in a gender-based violence survey conducted in a low-income setting in South Africa. Results Some participants reported motives for survey participation which could be interpreted as altruistic. Their motives included a desire to contribute to advancement of knowledge and to share life experiences so that unknown others could learn from these experiences. Yet, some participants hoped their participation will result in personal benefit or that they may be helped with their socio-economic challenges. The analysis further revealed a complex relationship between altruism and self-interest motives for participating in the survey amongst some of the participants. Conclusion We conclude that it is difficult to discern which motive was primary or preceded the other. This is because such motives are not fixed, probably multiple and owing to their fluidity, may shift in people's minds at different times and depending on the nature of the conversation. Moreover, there may be a shift in the weight given to different motives over time.